Hearing voices: does it give your patient a headache? A case of auditory hallucinations as acoustic aura in migraine - Van der Feltz-Cornelis CM (Dove Medical Press, 2012)
Christina M van der Feltz-Cornelis1–3, Henk Biemans1, Jan Timmer11Clinical Centre for Body, Mind and Health, GGz Breburg, Tilburg, The Netherlands; 2Faculty of Social and Behavioral Sciences, Tilburg University, Tilburg, The Netherlands; 3Trimbos Instituut, Utrecht, The NetherlandsObjective: Auditory hallucinations are generally considered to be a psychotic symptom. However, they do occur without other psychotic symptoms in a substantive number of cases in the general population and can cause a lot of individual distress because of the supposed association with schizophrenia. We describe a case of nonpsychotic auditory hallucinations occurring in the context of migraine.Method: Case report and literature review.Results: A 40-year-old man presented with imperative auditory hallucinations that caused depressive and anxiety symptoms. He reported migraine with visual aura as well which started at the same time as the auditory hallucinations. The auditory hallucinations occurred in the context of nocturnal migraine attacks, preceding them as aura. No psychotic disorder was present. After treatment of the migraine with propranolol 40 mg twice daily, explanation of the etiology of the hallucinations, and mirtazapine 45 mg daily, the migraine subsided and no further hallucinations occurred. The patient recovered.Discussion: Visual auras have been described in migraine and occur quite often. Auditory hallucinations as aura in migraine have been described in children without psychosis, but this is the first case describing auditory hallucinations without psychosis as aura in migraine in an adult. For description of this kind of hallucination, DSM-IV lacks an appropriate category.Conclusion: Psychiatrists should consider migraine with acoustic aura as a possible etiological factor in patients without further psychotic symptoms presenting with auditory hallucinations, and they should ask for headache symptoms when they take the history. Prognosis may be favorable if the migraine is properly treated. Research is needed to explore the pathophysiological mechanism of auditory hallucinations as aura in migraine.Keywords: auditory hallucination, acoustic aura, migraine, psychosis, DSM-IV, case report